Upaya Peningkatan Kualitas Pengurus Remaja Masjid di Masjid Ikhwanul Muhajirin - Yendra, Wahyu; Ananda Arif, Muhammad; Putra Adriyan, Dendi; Setiawan, Yoga (Yayasan Inovasi Akademi Nusantara, 2024)
Leadership is the use of influence or power possessed in a device or organization, which of these influences produces something that has a direct impact on the achievement of the goals to be achieved by the organization. The purpose of this study is to determine how influential the role of leadership is in efforts to improve the quality of youth mosque administrators at the Ikhwanul Muhajirin Mosque located in the Mega Permai I Complex, Koto Tangah District, Padang Sarai Village, Padang. This study uses a qualitative research type. The research conducted was carried out in order to better apply situational leadership theory and collaborate it with a democratic leadership type. And the assessment or conclusion regarding it can be seen later from the composition of decisions and actions in the Islamic youth organization of the mosque which is carried out by deliberation or together and seen from the interaction between members of the Islamic organization of the mosque and also the interaction between the chairman and members.